(untitled) (Journal of Current and Advance Medical Research, 2020)
Background: Desarda hernia repair has emerged as a recognized operative method for inguinal hernia repair. Objective: The purpose of the present study was to see the outcome of emergency inguinal hernia repair by Desarda technique. Methodology: This was an observational study was carried out in the Department of Surgery at Sher-E-Bangla Medical College Hospital, Barisal, Bangladesh and Private Hospital, Narayanganj, Bangladesh from August 2015 to January 2017. Twenty patient was operated by Desarda technique. Variables includes age, operating time, post-operative complications, post-operative hospital stay, cost of the procedure, chronic groin pain and any early recurrence. Result: Mean age of patient 50.25±18.9, Mean operating time was 78.4±9.64 mins. Majority 16 patient experienced mild post-operative pain measured in VAS score. Mean with SD of hospital stay was 5.05±2.16 days. Patient had developed different post-operative complications like wound infection in 2(10.0%) cases, scrotal edema in 5(25.0%) cases, seroma formation in 1(5.0%) case and no early recurrence and. Conclusion: In this study, it revealed that Desarda repair was associated with less post-operative complications, less post-operative pain, zero recurrence rate, no chronic groin pain and performed in emergency cases. So it is safe and most reliable technique for complicated (Incarcerated, Obstructed, Strangulated) inguinal hernia. Journal of Current and Advance Medical Research 2020;7(1): 44-48